Mesenteric cava anastomosis - Praderi, Raul C.; Mazza, Milton; Gomez Fossati, Carlos; Ituño, Carlos; Turturiello, Horacio; Kaufmann, Pedro (Cirugía del Uruguay, 1975)
The authors discuss the technique of meso-caval shunts in its three historical stages: first, end to-end, then, side-to-end -the latter was used in 2 cases of portal thrombosis and in 3 of cirrhosis- and finally, with an interposition "H" graft. with autogenous vein or a Dacron's prosthesis. It may be necessary in portal thrombosis of splenectomized adults or in little children with a splenic vein of less than 1 cm diameter. In cirrhosis this technique is of choice when the hepatic pedicle cannot be reached and the patient has been splenectomized or when one does not want to resect a very large and attached spleen. The two patients with thrombosis had a satisfactory evolution and 2 of the cirrhotic ones stopped bleeding. However, all of the latter died during the post-operative course: 2 of them due to hepatic dysfunction and coma and the third one with a severe respiratory complication. In all cases they were patients of high risk, belonging to the "C" group of Child's classification.